The Iron-Ore Problem of Lorraine - Berglund, Abraham (Quarterly Journal of Economics, 1919)
Importance of iron-ore reserves of Lorraine, 531. — Comparison with reserves of other countries, 534. — Quality and location of French reserves, 535. — Dependence of German steel industry upon Lorraine, 536.— Also of French steel industry, 538. — Probable French policy of control, 540. — Coal production of France and Germany, 544. — Importance of the Saar district, 547. — German pre-war view of importance of controlling iron in the interest of militancy, 552.